SHARIA CAPITAL MARKET LITERACY IN EDUCATIONAL INSTITUTIONS IN TADIKA AL FIKH ORCHARD MALAYSIA - Isra , Isra Hayati; Afandi, Ahmad; Sami Gultom, Mitra (Berajah Journal, 2024)
This program is a community service initiative that aims to improve staff understanding and skills in the principles of Islamic economics and Islamic capital markets. Conducted at Tadika Al Fikh Orchard, an early childhood education institution in Malaysia, the program targets teaching and management staff to strengthen Islamic financial literacy. The activity will occur from 3 to August 8, 2023, involving 40 participants led by Puan Hj. Siti Ruzita Ramli, Chairman of Tadika Al Fikh Orchard.This activity explores the effectiveness of training programs that include lessons on Islamic mutual funds, stocks, Sukuk, and other Islamic financial instruments. Program implementation methods include identifying partner problems, conducting interactive training, and evaluation through pre-test, post-test, and questionnaire. The program results showed a significant improvement in participants' understanding of Islamic capital markets, as evidenced by an increase in average scores from pre-test to post-test. The evaluation showed that the training improved the understanding and practical application of Islamic economic principles and capital markets. The implications of this program are broad, enhancing individual capabilities and positively impacting Islamic financial education in the context of educational institutions and the wider community.